Management of aluminium phosphide poisoning with a holistic approach at NHL municipal medical college and hospital, Ahmedabad - Dheeraj B More; Mahendra N Wankhede; Harshad Malve (Wolters Kluwer Medknow Publications, 2022)
Background: Aluminium phosphide is a usual ingredient of rodenticide and its poisoning is a common cause of suicide in India. Signs and symptoms of its toxicity are well-known. Its toxic effects are mainly due to liberation of phosphine gas which causes cell hypoxia due to inhibition of oxidative phosphorylation and results in circulatory failure. Aims and Objectives: Mortality with aluminium phosphide is high as there is no specific antidote available yet. And hence we need to explore holistic treatment approach to improve patient outcomes in aluminium phosphide poisoning. Materials and Methods: Present study discusses a holistic treatment approach to aluminium phosphide poisoning in this retrospective analysis of 100 cases from a tertiary care hospital in this study. Results: Around 65% patients survived due to the holistic treatment approach and correct treatment protocol with supportive therapy. Conclusions: The aggressive and appropriate management with continuous hemodynamic monitoring and holistic treatment approach can reduce the mortality significantly in aluminium phosphide poisoning.